Why should it matter what commodity is the source of agricultural profits? Dairy development in India - Alderman, Harold (International Food Policy Research Institute, 1994)
In 1896, an obscure out-of-office politician rose to prominence and the Democratic presidential nomination on the basis of a rousing speech condemning the gold standard. Working up to the conclusion of that oratory, William Jennings Bryan claimed: "the great cities rest upon our broad and fertile prairies. Burn down your cities and leave our farms, and your cities will spring up again as if by magic; but destroy our farms and the grass will grow in the streets of every city in the country (Bryan 1967)."